Targeting DNA mismatch repair pathway by CRISPR nanosystem for boosting checkpoint blockade cancer immunotherapy. (August 2022) - Dong, Xue; Pan, Pei; Zhang, Qiu-Ling; Ye, Jing-Jie; Bao, Peng; Zeng, Xuan; Zhang, Xian-Zheng
Abstract: Immune checkpoint blockade (ICB) therapy has exhibited great clinical benefits in multiple cancers types. However, most cancer patients such as colorectal cancers (CRC) show poor response to ICB. Here, we develop a magnetic nanoparticle (MNP)-mediated delivery of CRISPR/Cas9 system (LMPM) to target the DNA repair pathway and inactivate endogenous DNA mismatch repair (MMR)-related Mlh1 gene as a new strategy of immunotherapy. The genetically knockout of Mlh1 can be effectively realized by CRISPR/Cas9 edition with external magnetic field control. As a consequence, the inactivation of Mlh1 lead to an increased tumor mutation burden and enhancement of tumor immunogenicity in situ, which can elicit strong antitumor immunity. Both in vitro and in vivo studies demonstrate that deploying such a strategy of targeting inactivation of Mlh1 shows high inhibition efficacy in the established tumors. In this way, tumor infiltration of CD8 + T cells and ICB response are significantly improved compared with α-PD1 monotherapy. In short, it is certified that precision targeting of DNA MMR pathway can boost specific anti-tumor immune response and display the potent potential in versatile tumor immunotherapy therapeutic exploitation. Graphical Abstract: Magnetic nanoparticle-mediated delivery of CRISPR/Cas9 system in vivo was reported for down-regulating DNA mismatch repair gene Mlh1 to increase tumor mutation burden and boost anti-tumor immune response. ga1 Highlights: Magnetic nanoparticle-mediated delivery of Cas9/sgMlh1 system effectively down-regulated Mlh1 both in vitro and in vivo . The inactivation of Mlh1 could increase the tumor mutation burden to enhance the tumor immunogenicity in situ . LMPM significantly facilitated the tumor-infiltrating of CD8 + T cells and potentiated ICB response.